2023
DOI: 10.12997/jla.2023.12.2.201
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Prevalence of Hypertriglyceridemia and Related Factors in Korean Adults: A Serial Cross-Sectional Study

Abstract: Objective We aimed to investigate the longitudinal trends in prevalence of hypertriglyceridemia in Korean adults and hypertriglyceridemia-associated lifestyle habits, socioeconomic factors and comorbidities. Methods Data from the 2007–2020 Korea National Health and Nutrition Examination Survey (KNHANES) were used in this study. Two cutoff values (≥150 mg/dL and ≥200 mg/dL) for fasting serum triglyceride levels were used to estimate the age- and sex-specific prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Although this effect seems rather moderate, it is similar in magnitude to the annual progression rates of mean CAL (0.02 mm/year) (Gatke et al, 2012). However, since previous studies had assumed that hypertriglyceridaemia peaks in middle age for men and increases throughout lifetime for women (Park et al, 2023), these effects may accumulate over time and be of greater clinical relevance in ageing societies.…”
Section: Discussionmentioning
confidence: 69%
“…Although this effect seems rather moderate, it is similar in magnitude to the annual progression rates of mean CAL (0.02 mm/year) (Gatke et al, 2012). However, since previous studies had assumed that hypertriglyceridaemia peaks in middle age for men and increases throughout lifetime for women (Park et al, 2023), these effects may accumulate over time and be of greater clinical relevance in ageing societies.…”
Section: Discussionmentioning
confidence: 69%
“…Finally, the associations between higher DunedinPACE and both lower HDL-C and higher TG were both stronger among those with a higher educational attainment. Studies also consistently reported that greater educational attainment and high levels of socioeconomic status are associated with elevated HDL-C levels [ 62 64 ], lower prevalence of hypertriglyceridemia [ 65 ], and lower epigenetic age [ 66 , 67 ]. Moreover, epigenetic age acceleration has been inversely associated with HDL-C and positively associated with TG levels [ 44 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…HTG has been overlooked for the last few decades because the focus of risk reduction was lowering of blood cholesterol (1,2). HTG has more recently been correlated with the incidence of stroke (3,4,5).…”
Section: Introductionmentioning
confidence: 99%